(untitled) (Biological Sciences - PJSIR, 1997)
Inhabitants of the Naranji village are known for their yellow colouration of teeth throughout the Mardan Division. A general survey ofthe area shows prevalence of dental and skeletal tluorosis of varied degree in the village. A detailed geochemical analysis of ground water of the village indicates fluoride concentration of 13.5 mg L-’ which is about 9 times more than WHO’s maximum contaminant level. The source of high fluoride in drinking water is considered to be the alkaline rocks of Koga Complex. Tube well water should be supplied to the area in order to avoid the HUOI-ide contamination.